MANUSIA KERJA DAN KESELAMATAN KERJA INDUSTRI PULP - Sulistyadi, Kohar; Sukamdani, Nugroho B (Universitas Sahid Surakarta, 2013)
Consumer demand for clean products and zero accident in theÂ industry makes to revise the implementation of the new wave of work in the prevention of accidents. Humans are often used as an excuse errors caused by accidents. To ensure the people who work and can be reached safety conditions necessary improvement efforts through several studies, namely: 1) The working environment (workspace, cleanliness, lighting, air circulation, temperature, humidity, noise), 2) Compliance food consumption and energy expenditure worker, 3) work space (seating and desk), 4) accident warning information, and 5) prevention and control of work. This Study provides advance information on potential safety in pulp industry